Telaah Kritis atas Gagasan Paradigma Islam Kuntowijoyo - Nurul Fajri (Refleksi: Jurnal Kajian Agama dan Filsafat, 1998)
This study critically examines the concept of the Islamic paradigm proposed by Kuntowijoyo, a prominent Indonesian scholar and cultural figure. Kuntowijoyo introduced the Islamic paradigm as an alternative approach to understanding and practicing Islam in the contemporary era, focusing on transformative thinking and social reconstruction. This study highlights the key elements of this paradigm, such as the concepts of historicism, prophetic ethics, and humanization, as well as their implications for Islamic thought and practice in Indonesia. Using textual analysis and a hermeneutic approach, this research evaluates the strengths and weaknesses of Kuntowijoyo's Islamic paradigm, including its relevance in addressing the challenges of modernity and globalization. The findings of this review are expected to contribute to the development of a more dynamic and contextual Islamic discourse in the future.